Pengembangan Modul Berbasis Augmented Reality Pada Materi Ikatan Kimia Di SMA Taman Mulia Pontianak - Rizki Bakdhu Wahyu Akbar; Raudhatul Fadhilah; Dini Hadiarti (Postgraduate, University of Mataram, 2024)
Onventional teaching media used by teachers in teaching chemical bonding has not been able to facilitate students in understanding the concept of chemical bonding because the media used are still in two-dimensional form. Therefore, it is necessary to develop three-dimensional teaching media capable of visualizing the concept of chemical bonding, one of which is augmented reality (AR). This study aims to determine the validity and practicality of an AR-based chemical bonding module. The research type used is Borg and Gall's development research model, modified into 7 research stages. The research sample consisted of 30 students selected using purposive sampling technique. The results of material, media, and language validation analysis indicate that the developed AR-based module is valid with validity percentages of 96.66%, 81.47%, and 88.33%, respectively. Practicality analysis using a practicality questionnaire shows that the developed AR-based module is practical with a practicality score of 93.88%. Therefore, the AR-based module is highly suitable as an alternative teaching media for the topic of chemical bonding